The impact of internet financial attributes and internet non-financial attributes on the entrepreneurial intention of college students - Jun, Li; Abd.Kadir, Hazlina (Edelweiss Applied Science and Technology, 2026)
With the rapid development of the internet, its inherent financial and non-financial attributes have significantly promoted the growth of national enterprises, particularly entrepreneurial activities among college students. Although online business loans have become increasingly prevalent, the evolution of the internet has also introduced new challenges to enterprises' financial needs to some extent. This study aims to explore the combined impact of Internet Financial Attributes and Internet Non-financial Attributes on college students' Entrepreneurial Intention. Employing a questionnaire survey method targeting students with innovation and entrepreneurship aspirations, it systematically analyzes how these attributes influence their Entrepreneurial Intention to identify key factors. The findings indicate that both the non-financial and Internet Financial Attributes exert a significant positive influence on college students' entrepreneurial intentions. Specifically, the Internet Financial Attributes positively impact entrepreneurial intentions through three dimensions: broadening financing channels, reducing financing costs, and enhancing financial risk perception. Meanwhile, the Internet Non-financial Attributes exert a positive influence by fostering entrepreneurship cultivation, promoting human capital accumulation, and strengthening innovation and entrepreneurship education. Based on these findings, this study proposes targeted policy recommendations centered on six key factors of financial and non-financial attributes, aiming to provide theoretical reference and practical guidance for entrepreneurial practices among Chinese college students.